Cross-listing and pricing efficiency: The informational and anchoring role played by the reference price - Chang, Eric C.; Luo, Yan; Ren, Jinjuan (Journal of Banking & Finance, 2013)
When a firm cross-lists its shares in segmented markets, the price of the first issued share, as a reference, plays both an informational and anchoring role in pricing the second issued share. We develop a model illustrating the dual-role. Empirically, we examine a group of Chinese firms that first issue foreign shares and then domestic A-shares, for which the anchoring effect adds to the A-share underpricing. Consistent with the model predictions, we find that the A-share underpricing is positively related to the difference in costs of capital in the two segmented markets, and that this positive association is weaker when participants are less likely to resort to the anchoring heuristic and when the A-share valuation involves less uncertainty.